Cosmotechnologies of Community and Collaboration in Vandana Singh’s Speculative Architectures - Joel P.W. Letkemann (Footprint)
Yuk Hui, referring both to climate change and its accompanying social upheavals, writes that ‘to confront the crisis that is before us’, humans will have to rethink the idea of technological universality and how it constructs our relationship to each other and to the natural world. For architects, this means considering how much architecture today is constrained by a singular technological paradigm, and how architects can think the many technologies of architecture differently.